2017
DOI: 10.4317/medoral.21436
|View full text |Cite
|
Sign up to set email alerts
|

Calcified carotid artery atheromas on panoramic radiographs of head and neck cancer patients before and after radiotherapy

Abstract: BackgroundThe aims of this study were to verify if head and neck radiotherapy (RT) is able to induce calcified carotid artery atheroma (CCAA) in a large head and neck cancer (HNC) population and also to compare the socio-demographic and clinical findings of patients with and without CCAA detected on panoramic radiographs.Material and MethodsPanoramic radiographs taken before and after head and neck radiotherapy (RT) of 180 HNC patients were selected and analyzed in order to identify the presence of CCAA. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…A total of 13,261 research articles were initially found in the databases after searching for all keywords. After applying the eligibility criteria and removing overlapping studies, 13,228 investigations were excluded, and a total of 33 studies 5 , 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 on the oral and maxillofacial effects of radiotherapy, as assessed by panoramic radiographs, were included. Table 1 summarizes the details of the selected studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 13,261 research articles were initially found in the databases after searching for all keywords. After applying the eligibility criteria and removing overlapping studies, 13,228 investigations were excluded, and a total of 33 studies 5 , 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 on the oral and maxillofacial effects of radiotherapy, as assessed by panoramic radiographs, were included. Table 1 summarizes the details of the selected studies.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the objectives of investigations pertaining to head and neck radiotherapy, 4 studies focused on determining whether radiotherapy may induce calcified carotid artery atheroma in patients with head and neck cancer, 16 35 38 39 and 2 studies exclusively examined patients with osteoradionecrosis by imaging. 17 31 The effects on oral structures such as teeth in children survivors of head and neck rhabdomyosarcoma was the subject of 4 investigations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Atheromatous plaques can accumulate at the carotid artery bifurcation and can be viewed on panoramic radiographs when they are calcified 9 . This type of imaging examination proved to be capable of detecting calcified atheromas in other systemic diseases, such as HIV infection, 10 chronic renal failure (CRF), 11,12 metabolic syndrome, dilated cardiomyopathy, 13 obstructive sleep apnea 14 and type‐2 diabetes, 15 including post‐menopausal women 14 .…”
Section: Introductionmentioning
confidence: 99%